Geminated Consonants in the Chronicle by Mula Mustafa Bašeskija - Filan, Kerima (Prilozi za orijentalnu filologiju, 2017)
The subject of this work are the geminated consonants in The Chronicle (Ljetopis) by Mula Mustafa Bašeskija, that were written in Turkish, with certain elementş of the Turkish used by the people of Bosnia and Hercegovina. This dialectic peculiarities are clearly shown by the way geminated consonants are vvritten. It has been discovered that Bašeskija wrote some of the Turkish